The Role of Zooplankton in Establishing Carbon Export Regimes in the Southern Ocean – A Comparison of Two Representative Case Studies in the Subantarctic Region - Halfter, Svenja; Cavan, Emma L.; Swadling, Kerrie M.; Eriksen, Ruth S.; Boyd, Philip W. (Frontiers in Marine Science, 2020)
Marine ecosystems regulate atmospheric carbon dioxide levels by transporting and storing photosynthetically fixed carbon in the ocean’s interior. In particular, the subantarctic and polar frontal zone of the Southern Ocean is a significant region for physically-driven carbon uptake due to mode water formation, although it is under-studied concerning biologically-mediated uptake. Regional differences in iron concentrations lead to variable carbon export from the base of the euphotic zone. Contrary to our understanding of export globally, where high productivity results in high export, naturally iron-fertilized regions exhibit low carbon export relative to their surface productivity, while HNLC (High Nutrient, Low Chlorophyll) waters emerge as a significant area for carbon export. Zooplankton, an integral part of the oceanic food web, play an important role in establishing these main carbon export regimes. In this mini review, we explore this role further by focusing on the impact of grazing and the production of fecal pellets on the carbon flux. The data coverage in the subantarctic region will be assessed by comparing two case studies - the iron-replete Kerguelen Plateau and the HNLC region south of Australia. We then discuss challenges in evaluating the contributions of zooplankton to carbon flux, namely gaps in seasonal coverage of sampling campaigns, the use of non-standardized and biased methods and under-sampling of the mesopelagic zone, an important area of carbon remineralization. More integrated approaches are necessary to improve present estimates of zooplankton-mediated carbon export in the Southern Ocean.